DYSBIOTIC UPPER AIRWAY DISORDERS IN CHILDREN WITH ACUTE STENOTIC LARYNGOTRACHEITIS LARYNGOTRACHEITIS - Zebo Farkhodovna Safoeva; Samiyeva Gulnoza Utkurovna (Scholar Express Journals, 2022)
In children, an increasing number of acute respiratory infections accompanied by airway obstruction very often leads to the development of stenotic laryngotracheitis. The primary factor in this is respiratory viruses, and bacterial flora often joins secondary to modify the course of the disease and determine its outcome. Exposure to infective agents in children promotes chronic infections of the respiratory tract, damaging the ciliary epithelium and weakening its connection with basal cells and the basal membrane, which contributes to the penetration of allergens and other inflammatory stimulants into the submucosal layer.
Keywords: respiratory tract; acute stenotic laryngotracheitis